1961
DOI: 10.3382/ps.0400368
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodism as a Factor in the Reproduction of the Turkey

Abstract: EXPERIMENT 1Procedure.-Beltsville Small White turkeys were hatched on December 18, 1955 and groups of 15 females each provided with 9 hours of light for 3 and 6 weeks 368 at University of British Columbia on July 1, 2015

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
1

Year Published

1962
1962
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 2 publications
0
11
1
Order By: Relevance
“…Effects of various lengths of photoperiod during the breeding season on fertility and hatchability have been reported by Mars-den et al (1962), McCartney et al (1961 and Shoffner et al (1962). Although the results varied, none of the reports contained evidence that these performance traits were significantly affected under differing light regimens.…”
mentioning
confidence: 77%
“…Effects of various lengths of photoperiod during the breeding season on fertility and hatchability have been reported by Mars-den et al (1962), McCartney et al (1961 and Shoffner et al (1962). Although the results varied, none of the reports contained evidence that these performance traits were significantly affected under differing light regimens.…”
mentioning
confidence: 77%
“…Although McCartney et al (1961), using out-of-season turkeys, reported no advantage for egg production in increasing daylength gradually, they reported a tendency for fertility and hatchability to be better under the gradual increase. However, the results of the two studies seem not to be comparable since the "gradual" increase described by McCartney et al consisted of 2-hour increments one week apart which might be considered "abrupt" when compared to the 30-minute daily increments and the 1^2-hour abrupt increase (9J/i to 11 hours) used in one phase of the present work.…”
Section: Resultsmentioning
confidence: 88%
“…Hamilton (1959) recommends a 14-to 16-hour light day obtained by increasing the lighting period in 1-hour daily increments. None of the above authors offered experimental evidence to support their recommendations but McCartney et al (1961), using out-ofseason turkeys, presented evidence indicating no advantage for egg production in increasing daylength gradually, 2 hours per week, from 9 to 15 hours, over an abrupt increase from 9 to 15 hours.…”
mentioning
confidence: 81%
“…Unlike the chicken, which will commence lay and continue to lay in continual darkness, (King, 1962;Morris et al, 1964), the turkey has a minimal photoperiod, something in excess of 10 hours (Wilson et al, 1962) below which no reproductive response can be obtained. The female turkey also has a dark period requirement in that it is relatively insensitive to stimulation unless it has previously received a long night, short day period (Harper and Parker, 1961;Leighton and Shoffner, 1961 a, b;McCartney et al, 1961;and Shoffner et al, 1962).…”
mentioning
confidence: 98%